Stahl’s ear correction: A review of surgical approaches - Aref Nassar; Joy Naba; Dollen Eid; Samer Abou Zeid; Joe Demian (JPRAS Open, 2025)
Background: Stahl’s ear is a congenital deformity involving an additional third crus and a pointed upper helix, leading to aesthetic and functional concerns. Surgical correction is often necessary for severe cases or when nonsurgical methods are ineffective. However, there is limited comprehensive guidance on surgical technique selection. Objectives: This review evaluates the full spectrum of surgical techniques for Stahl’s ear correction, aiming to provide a comparative framework for surgical decision-making. Methods: A systematic search of PubMed, MEDLINE, and Embase databases identified 18 studies published through October 2024. Data on surgical techniques, outcomes, and complications were extracted and synthesized. Results: The review analyzes surgical techniques for Stahl’s ear correction, evaluating their advantages, limitations, and clinical applications. Surgical methods were categorized into cartilage-sparing and cartilage-cutting techniques, with combined approaches also discussed. A comprehensive comparison of techniques is provided, consolidating scattered data into a practical guide for tailoring treatment to patient-specific anatomy. Conclusions: Surgical correction of Stahl’s ear requires a patient-centered approach, balancing deformity severity and cartilage characteristics. This study presents the first comprehensive review of surgical techniques for correcting Stahl’s ear deformity, providing a detailed analysis of their advantages, limitations, and clinical indications. Further research is needed to evaluate long-term outcomes and refine evidence-based guidelines.